Pemikiran Dakwah K.H. Miftah Faridl tentang Moral dalam Buku “Hikmah Kehidupan” - M. Rafki Razif Kiransyah; Nia Kurniati; M. Fauzi Arif (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. The moral crisis in this era of globalization and digitalization requires a relevant da'wah figure in fostering the character of the people. This study examines K.H. Miftah Faridl's da'wah thoughts on moral values in the book